Simulation of the emergency evacuation about social groups in a complex subway station - Huang, Lin; Li, Wenhang; Gong, Jianhua (Physica A, 2024)
In order to study the crowd evacuation process in complex subway stations, this paper proposes a social group perception evacuation model based on the social group evacuation model and the perception evacuation model, combined with the spatial index algorithm and the social group random algorithm, and takes a real subway station as an example to simulate the crowd evacuation process. Through the simulation results, the evacuation bottlenecks in the subway station are analyzed and the influence of social groups on evacuation efficiency is also verified. The results show that subway gates, fenced aisles and exits are important bottlenecks for crowd evacuation in subway stations, and the social groups will reduce the evacuation efficiency. This model can more truly restore the interaction behavior between evacuees and the environment in the evacuation process, and is suitable for the real complex subway stations. •Bottlenecks that affecting evacuation efficiency in subway stations mainly include subway gates, fenced aisles and exits.•Social groups have an important effect on evacuation efficiency.•The variation trends of panic index of individuals and social groups under different desired velocities are basically the same.